Bimetallic basic catalyst comprising niobium and cesium supported on MCM-48 for the Claisen-Schmidt condensation - Endud, Salasiah (2012)
The Claisen–Schmidt condensations stand out to be important reaction in carbon–carbon bond formation as well as in the preparation of fine chemicals and intermediates with the presence of base catalyst such as NaOH. However, only few studies concern the synthesis and catalytic activity of mesoporous silica containing bimetallic compound as catalyst for aldol condensation of bulky aldehydes. The advantages of mesoporous systems with respect to zeolites are the improved reactant accessibility to the active sites and enhanced catalyst stability. Mesoporous silica with exceedingly high surface area (> 800 m2/g) and very high concentration of surface silanol groups fulfill most of the criteria for catalyst support. In this contribution, we report on the incorporation of Nb and Cs, alone or together, into the mesoporous silica with cubic mesostructure and the investigation of their catalytic properties in the Claisen-Schmidt condensation of acetophenone with benzaldehyde to produce chalcone, an aromatic ketone that forms the active sites for important biological compounds with antibacterial activities.